Esmirtazapine treatment of postmenopausal vasomotor symptoms: two randomized controlled trials. (4th May 2019) - Birkhaeuser, M.; Bitzer, J.; Braat, S.; Ramos, Y.
Abstract: Objectives: Two identical 12-week, randomized, double-blind, placebo-controlled, multi-arm, parallel-group Phase III studies (Study P012, NCT00560833; Study P013, NCT00535288) evaluated the efficacy and safety of esmirtazapine, an investigational medicine, for the treatment of moderate to severe vasomotor symptoms (VMS) in postmenopausal women. Methods: Participants were randomized to placebo or esmirtazapine (2.25, 4.5, 9.0, or 18.0 mg). Co-primary efficacy endpoints (daily frequency and severity of moderate to severe VMS, both at weeks 4 and 12) were based on participative LogPad daily diaries. Adverse events (AEs) were recorded. Results: In Studies P012 and P013, 942 and 946 participants were randomized, respectively. Compared with placebo, esmirtazapine significantly reduced the mean daily frequency by 1.4–2.2 moderate to severe VMS at weeks 4 and 12 (both ≥4.5 mg) and mean daily severity by 0.06–0.08 symptoms at weeks 4 (≥4.5 mg) and 12 (9.0 mg P012; 18.0 mg P013 only). Esmirtazapine was generally well tolerated with a more favorable safety profile at lower doses. Somnolence and fatigue were the most frequently reported AEs. Conclusions: Esmirtazapine reduced the frequency and severity of moderate to severe VMS associated with menopause and was generally well tolerated in the study population.